Ethics and Law in Clinical Practice: Principals of How to Understand an Ethical Dilemma - Firmansyah, Yohanes; Utomo, St. Laksanto (International Journal Labs, 2022)
Background: In the current global era, the medical profession is one of the professions that gets the spotlight. The spotlight on the medical profession is a sign that currently some people are not satisfied with health services and the service of the medical profession in the community. Patient dissatisfaction occurs because of unbalanced communication between doctors and patients, there is no relationship of trust between doctors and patients in the relationship that occurs. Aim: Based on the above background, the purpose of this study is to discuss clinical ethics, health law and their implementation in clinical practice. Method: The type of research that was be used in this journal research is normative legal research. Normative legal research examines law from an internal perspective with the object of research being legal norms. Findings: One of the simple things in the implementation of clinical ethics is the application of informed consent in clinical practice. Informed consent has a dual role in upholding the rights of patients and on the other hand protecting doctors in the face of lawsuits.